Moderkærlighedens kriminelle dimensioner - Om krimi, melodrama og humanistisk kulturkritik i Kerstin Ekmans prisbelønnede roman "Händelser vid vatten" - Hejlsted, Annemette (Women, Gender & Research, 1998)
Kerstin Ekman is one of the greatest female authors in Nordic literature. In 1994, she was awarded the Nordic Council Literature Prize for her novel "Events by the Water". This article makes a study of Ekman's masterpiece, examining how the novelist - by combining the strategies of the crime novel with those of melodrama - focuses on the concept of maternal love as an inherent and given value. What Ekman offers, the article concludes, is a revised humanist basis for evaluating maternal love as well as humans' relationship with each other and with Nature, based on a rethink of the human subject as the sum of memories.